The practices of property manager in preserving the appreciating value of high rise residential building / Nur Zaireen Zhafareena Zahari and Thuraiya Mohd - Zahari, Nur Zaireen Zhafareena; Mohd, Thuraiya (2019)
Good management of building able to upgrade the quality of buildings that remain long lifespan, minimizing deterioration rate and dysfunctional as well as to prolong the value. The trend now, perceived to have a better living environment coupled with tightened safety and quality measures. Building owner chooses to be more advanced not only just buying a property but need a better lifestyle. By achieving high return may preserve appreciate value of the building by conserve the structure as well as resulted in appearance. Property management in Malaysia mostly still in the infancy stage and left behind compared system practice with other developed countries.The management system approach is lack of professionalism and free hand in managing. This research aims to investigate a comprehensive management regarding residential building in Malaysia. Qualitative approach use in this research, to determine the practices of property manager in preserving appreciating value of high rise residential building. Five (5) property managers were interviewed by using a semi-structured interview to gauge their perceptions in management of building. Findings from the analysis show that the five (5) attributes should be considered in managing the building.These findings offering a significant input to property manager, owner and investor in providing enhancement to professionalism in property management.